Persistent Cognitive Alterations in Rats after Early Postnatal Exposure to Low Doses of the Organophosphate Pesticide, Diazinon - Timofeeva, Olga A. (2007)
BACKGROUND: Developmental neurotoxicity of organophosphorous insecticides (OPs) involves multiple mechanisms in addition to cholinesterase inhibition. We have found persisting effects of developmental chlorpyrifos (CPF) and diazinon (DZN) on cholinergic and serotonergic neurotransmitter systems and gene expression as well as behavioral function. Both molecular/neurochemical and behavioral effects of developmental OP exposure have been seen at doses below those which cause appreciable cholinesterase inhibition. OBJECTIVES: We sought to determine if developmental DZN exposure at doses which do not produce significant acetylcholinesterase inhibition cause cognitive deficits. METHODS: Rats were exposed to DZN on postnatal days 1-4 at doses (0.5 and 2 mg/kg/d) that span the threshold for cholinesterase inhibition. They were later examined with a cognitive battery tests similar to that used with CPF. RESULTS: In the T-maze DZN caused significant hyperactivity in the initial trials of the session, but not later. In a longer assessment of locomotor activity no DZN-induced changes were seen over a 1-hour session. Prepulse inhibition was reduced by DZN exposure selectively in males vs. females; DZN eliminated the sex difference present in controls. In the radial maze, the lower but not higher DZN dose significantly impaired spatial learning. This has previously been seen with CPF as well. The lower dose DZN group also showed significantly greater sensitivity to the memory-impairing effects of the anticholinergic drug scopolamine. CONCLUSIONS: Neonatal DZN exposure below the threshold for appreciable cholinesterase inhibition caused neurocognitive deficits in adulthood. The addition of some inhibition of AChE with a higher dose reversed the cognitive impairment. This non-monotonic dose-effect function has also been seen with neurochemical effects. Some of the DZN effects on cognition resemble those seen earlier for CPF, some differ. Our data suggest that DZN and CPF affect transmitter systems supporting memory function, differently, implying participation of mechanisms other than their common inhibition of cholinesterase.